AXIOLOGICAL SPECIFICITY OF THE CONCEPT “STRANGE” (AS EXEMPLIFIED IN THE AMERICAN NOVEL BY GEORGE R. R. MARTIN “A DANCE WITH DRAGONS”) - Olga I. Agafonova , Irina V. Belkina , Marina S. Belozerova , Anna Y. Vorobiyova , Yulia N. Yatsenko , Margarita V. Kychkova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The paper deals with the study of explicit and implicit evaluative meanings of the concept “strange” by means of the example of some quotes from George Martin’s American novel A Dance with Dragons. The article discusses the two fundamental concepts of the axiological world picture – value and evaluation. From the perspective of axiological linguistics, everything that is valuable is reflected in the language appraisal, which depends on unstable subjective and objective value judgments. The purpose of this paper is an axiological analysis of the concept “strange” in modern English worldview, intellectual and emotional characteristics of not only a certain linguistic personality but also of society on the whole are revealed via studying the concepts. An axiological analysis of the concept “strange” in the literary work reveals evaluative connotations of the main characters, which render their value-based consideration, which, bereft of their context, can be interpreted differently. Thus, the study reveals that implicit and explicit value judgments are dependent on the subjective interpretation of the linguistic identity